2020
DOI: 10.1021/acs.iecr.9b06356
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Modeling of Water-Alternating-Gas Injection and Foam-Assisted Chemical Flooding for Enhanced Oil Recovery

Abstract: History-matching of core-flood experimental data through numerical modeling is a powerful tool to get insight into the relevant physical parameters and mechanisms that control fluid flow in enhanced oil recovery processes. We conducted a mechanistic numerical simulation study aiming at modeling previously performed water-alternating-gas and foam-assisted chemical flooding core-flood experiments. For each experiment, a one-dimensional model was built. The obtained computed tomography scan data was used to assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The effectiveness of numerical simulation studies on chemical flooding showed far‐reaching consequences during oilfield applications, as evident from the findings of earlier papers 37,40 . This kind of grid‐based model helps in understanding fluid flow behavior prior to injection; as well as achieve a sufficiently robust model 36,38,39 . Table 1 presents the core and fluid properties employed in STARS.…”
Section: Experimental and Simulationmentioning
confidence: 80%
See 1 more Smart Citation
“…The effectiveness of numerical simulation studies on chemical flooding showed far‐reaching consequences during oilfield applications, as evident from the findings of earlier papers 37,40 . This kind of grid‐based model helps in understanding fluid flow behavior prior to injection; as well as achieve a sufficiently robust model 36,38,39 . Table 1 presents the core and fluid properties employed in STARS.…”
Section: Experimental and Simulationmentioning
confidence: 80%
“…Druetta and co‐workers developed a flooding simulator to investigate EOR properties of different chemical fluid compositions 38 . Janssen et al found that CMG simulation model is useful to determine displacement phenomena governing flooding behavior, depending on injection fluid type 39 . The effectiveness of numerical simulation studies on chemical flooding showed far‐reaching consequences during oilfield applications, as evident from the findings of earlier papers 37,40 .…”
Section: Experimental and Simulationmentioning
confidence: 97%
“…The effectiveness of numerical simulation studies on chemical flooding showed far-reaching consequences during oilfield applications, as evident from the findings of earlier papers [34,37]. This kind of grid-based model helps in understanding fluid flow behavior prior to injection; as well as achieve a sufficiently robust numerical model [33,35,36]. Table 1 presents the core and fluid properties employed in STARS model.…”
Section: Simulation Methodologymentioning
confidence: 86%
“…Druetta and co-workers [35] developed a flooding simulator to investigate EOR properties of different chemical fluid compositions. Arhuoma et al [36] found that CMG simulation model is useful to determine displacement phenomena governing flooding behavior, depending on injection fluid type. The effectiveness of numerical simulation studies on chemical flooding showed far-reaching consequences during oilfield applications, as evident from the findings of earlier papers [34,37].…”
Section: Simulation Methodologymentioning
confidence: 99%
“…Mechanistic numerical simulation also can be carried out to model previous WAG and foam-assisted chemical flooding core-flood experiments (Janssen et al, 2020). In addition, a 1-D model was built to obtain tomography scan data and assign varying porosity and permeability to each grid.…”
Section: Introductionmentioning
confidence: 99%